2021
DOI: 10.1186/s40104-021-00607-w
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the effectiveness of in ovo feeding of vitamin C based on the embryonic vitamin C synthesis and absorption in broiler chickens

Abstract: Background Many researches about in ovo feeding (IOF) of vitamin C (VC) are gradually carried out to explore physiological development in chicken, but little studies focus on VC synthesis capacity of the embryo itself, the selection of injection site and the effectiveness of IOF of VC. This study aims to explore the above problems. Results Kidney and yolk sac were the main organs for VC synthesis and L-gulonolactone oxidase (GLO) expression was low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The HPLC procedure utilized in this experiment was more sensitive and accurate for detecting low levels of AA compared to the spectrophotometric analysis, resulting in more reliable results that reflect the dynamic of AA synthesis in broilers. In addition, it is worth noting that chicken embryos have the capacity to synthesize AA in the kidney (metanephros and mesonephros) and yolk sac membrane, with synthesis rates increasing with the development stage [ 23 , 24 ]. The high biosynthesis rate of broilers at hatching explains their high need for AA, as they grow rapidly and are exposed to a complex environment that requires a greater amount of AA to cope with.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The HPLC procedure utilized in this experiment was more sensitive and accurate for detecting low levels of AA compared to the spectrophotometric analysis, resulting in more reliable results that reflect the dynamic of AA synthesis in broilers. In addition, it is worth noting that chicken embryos have the capacity to synthesize AA in the kidney (metanephros and mesonephros) and yolk sac membrane, with synthesis rates increasing with the development stage [ 23 , 24 ]. The high biosynthesis rate of broilers at hatching explains their high need for AA, as they grow rapidly and are exposed to a complex environment that requires a greater amount of AA to cope with.…”
Section: Discussionmentioning
confidence: 99%
“…The increased AA levels in both livers and spleens indicate the increasing requirement of AA in broilers as they grow. In ovo injection of AA has been reported to have positive effects on posthatch growth and the antioxidant capacity of broilers [ 24 , 33 ]. A previous study also indicated that supplementing broilers’ diets with AA induced lower GLO enzyme activities while increasing concentrations of AA in livers and spleen, resulting in better production performance and enhanced antioxidant ability [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The abundance of the transporters and the pattern of mRNA expression of the transporters could dictate the choice of routes. Such as, the yolk sac translates a higher amount of sodium-dependent vitamin C transporter 1 (SVCT1) than amnion and is considered the optimum route for vitamin C inoculation ( 88 ).…”
Section: Routes and Time Of In Ovo Deliverymentioning
confidence: 99%
“…Zhang et al ( 17 ) also reported that IOF of 3 and 6 mg ascorbic acid increased body weight (BW), average daily gain (ADG), and average daily feed intake (ADFI) during the grower phase (Day 14–28), but a high dose (36 mg) negatively impacted growth performance, and 12 mg beneficially decreased plasma Malondialdehyde at the grower and finisher phase of a bird's life ( 17 ). IOF of vitamin C increased plasma level of vitamin C in newly hatched chicks, decreased embryonic mortality, and increased hatchability ( 18 , 88 ).…”
Section: In Ovo Delivered Bioactive Compounds and Their Effectsmentioning
confidence: 99%
“…In ovo feeding (IOF) is a viable method that delivers appropriate nutrients to the amnion at the later stages of the embryo (10,11). Numerous studies have demonstrated that IOF of exogenous nutrients plays a positive role in embryonic development and post-hatching performance in poultry (12)(13)(14)(15). L-arginine (Arg) is a nutritionally essential amino acid for poultry and has many biological and physiological functions (16), one of the primary functions is to synthesize protein for supporting cell growth.…”
Section: Introductionmentioning
confidence: 99%